Artificial Mn4Ca Clusters with Exchangeable Solvent Molecules Mimicking the Oxygen‐Evolving Center in Photosynthesis. Issue 12 (29th January 2019) - Chen, Changhui; Chen, Yang; Yao, Ruoqing; Li, Yanxi; Zhang, Chunxi
Abstract: The natural Mn4 Ca cluster in photosystem II serves as a blueprint to develop artificial water‐splitting catalysts for the generation of solar fuel in artificial photosynthesis. Although significant advances have recently been achieved, it remains a great challenge to prepare robust artificial Mn4 Ca clusters that precisely mimic the structure and function of the biological catalyst. Herein, we report the isolation and structural characterization of two Mn4 CaO4 complexes with polar solvent molecules, acetonitrile or N, N‐dimethylformamide, which closely mimics the two water molecules on the calcium ion, as well as the oxidation states of the four manganese ions and the main geometric structure of the natural Mn4 Ca cluster. These new artificial Mn4 Ca complexes provide important chemical clues to understand the structure and mechanism of the biological system. Abstract : Mimic : It is a great challenge to prepare robust artificial Mn4 Ca clusters that precisely mimic the oxygen‐evolving center (OEC) in natural photosynthesis. Two Mn4 CaO4 complexes are prepared which closely mimic the exchangeable solvent molecules on the Ca center, the oxidation states of the four manganese ions, and the main structure of the natural OEC.